Administrating the Admission and Grouping Policies of the Preschool - Coonrod, Debbie; Debcon, Inc., Bloomington, IN. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Factors used in selecting children for admission to preschool programs and factors that determine the way children are grouped within preschool programs are discussed. Factors that affect the composition and number of children admitted to a program are said to include funds, number of staff available, size of facility, current legislation and regulations about facilities, characteristics of children (such as age, handicaps, or success in toilet training), characteristics of parents (such as economic status or willingness to participate in the preschool program), priorities given to siblings, race, language, abilities and/or limitations of the staff or facilities. It is suggested that once children are admitted, considerations for grouping should depend on how to make best use of staff in meeting the individual needs of children in their growth and development. The two most familiar grouping patterns, mixed-age and same-age groupings, are described. Three advantages of the mixed-age pattern ("family grouping") are cited: (1) younger children show greater progress than in same-age groupings, (2) children can follow their own interests, and (3) teaching is continuous from year to year because the population tends to remain constant. Disadvantages of same-age grouping are noted. Other grouping patterns include developmental grouping based on ability level, grouping based on sex, grouping based on self-selection of the child, and grouping based on socio-economic differences or disabilities. (SS)
Availability: Debcon, Incorporated, 4503 North Northwoods Lane, Bloomington, IN 47401 (Cassette tape, $10.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ability Grouping; Admission Criteria; Age Groups; Day Care; Disabilities; Grouping (Instructional Purposes); Heterogeneous Grouping; Homogeneous Grouping; Preschool Education; Selective Admission; Opinion Papers; Guides, Non-Classroom.